YouTube as a source of information for hidradenitis suppurativa treatment - Milosz Lewandowski; Zuzanna Swierczewska; Wioletta Baranska-Rybak (Wolters Kluwer Medknow Publications, 2022)
Background: Hidradenitis suppurativa (HS) is a chronic, inflammatory skin disease characterized by a significant decrease in the patients' quality of life. Patients are increasingly looking for information about HS on social media, including YouTube (YT). However, the quality of the videos in some other diseases has been often scored as poor. Objectives: The aim of this study was to evaluate the usefulness and the quality of the most viewed acne inversa videos on YT. Methods: YT was searched for the keywords "HS" and "acne inversa." For videos, quality assessment validated DISCERN instrument and the global quality score (GQS) were applied. Furthermore, the popularity of each video using the video power index (VPI) score was evaluated. Results: After applying the exclusion criteria, 34 videos were analyzed. We found that video quality was poor regardless of video type. The mean DISCERN score between the raters was 34.65 ± 10.7, and the mean GQS score was 2.6 ± 0.98. There was no significant correlation between the DISCERN, GQS and VPI, the number of views, likes, dislikes, comments, and video duration. Conclusion: Our study highlights the gaps in knowledge regarding HS treatment on YT. Hence, this information can be used to create superior educational content in the future.